Cylindrical secondary battery and electronic device

By setting stripes on the second negative electrode material layer of the negative electrode sheet and optimizing the Si element content in the first negative electrode material layer, the problem of insufficient wetting in the middle of the cylindrical lithium-ion battery electrode sheet is solved, and the lithium-elimination performance and cycling performance of the battery are improved.

CN120226160APending Publication Date: 2025-06-27XIAMEN AMPACE TECH LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380073671.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-27
Publication Date
2025-06-27

AI Technical Summary

Technical Problem

In the full-pole ear-soft structure, the middle of the electrode sheet is poorly wet, affecting the battery performance, and the mass loss of the active material of the electrode sheet leads to lithium evolution.

Method used

The second negative electrode material layer of the negative electrode sheet is provided to improve the wetting performance of the electrolyte on the negative electrode sheet. The mass percentage of Si element in the first negative electrode material layer is greater than that of the second negative electrode material layer, and the depth, width and density of the fringes are regulated to improve the permeability of the electrolyte.

Benefits of technology

By improving the wetting performance of the electrolyte, reducing the capacity loss and volume expansion risks caused by the fringe setting, the lithium-ion performance and circulation performance of the cylindrical secondary battery are effectively improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120226160A_ABST
    Figure CN120226160A_ABST
Patent Text Reader

Abstract

The invention provides a cylindrical secondary battery and an electronic device, the cylindrical secondary battery comprises a negative electrode plate, the negative electrode plate comprises a negative electrode current collector and a negative electrode material layer located on at least one surface of the negative electrode current collector, and the negative electrode material layer comprises a first negative electrode material layer and a second negative electrode material layer. The first negative electrode material layer is located between the negative electrode current collector and the second negative electrode material layer, the first negative electrode material layer and the second negative electrode material layer both comprise a silicon-based material, and based on the mass of the negative electrode material layer, the mass percentage content of the Si element in the first negative electrode material layer is greater than the mass percentage content of the Si element in the second negative electrode material layer. The second negative electrode material layer is provided with a plurality of stripes, the stripes extend along the width direction of the unfolded negative electrode plate, and the stripes are arranged at intervals along the length direction of the unfolded negative electrode plate. Through the arrangement, the electrolyte has good infiltration performance on the negative pole piece, and the cylindrical secondary battery has good lithium precipitation performance and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of electrochemistry technology, and particularly to a cylindrical secondary battery and an electronic device. Background Art

[0002] Cylindrical secondary batteries, such as cylindrical lithium-ion batteries, are applied to various high-rate discharge systems (such as a discharge rate greater than 3C), and have characteristics such as high specific energy, high working voltage, low self-discharge rate, small size, and light weight, and are widely used in the field of consumer electronics.

[0003] Currently, the design of high-power cylindrical lithium-ion batteries usually adopts a full tab design, that is, the positive tab and the negative tab extend from opposite directions, and a full tab cutting and folding or flattening technology is used for preparation. However, the full tab flattening structure will bring problems of electrode sheet infiltration, especially poor infiltration in the middle of the electrode sheet, which affects the performance of the lithium-ion battery. Currently, an electrode sheet punching technology can be used to improve the wettability of the electrode sheet, but it will cause a loss of the mass of the active material of the electrode sheet, resulting in the occurrence of lithium plating phenomenon. Summary of the Invention

[0004] The purpose of this application is to provide a cylindrical secondary battery and an electronic device to improve the lithium plating performance and cycling performance of the secondary battery. The specific technical solutions are as follows:

[0005] It should be noted that in the summary of the invention of this application, a lithium-ion battery is used as an example of the secondary battery to explain this application, but the secondary battery of this application is not limited to lithium-ion batteries.

[0006] The first aspect of the present application provides a cylindrical secondary battery. The cylindrical secondary battery includes a negative electrode plate, and the negative electrode plate includes a negative electrode current collector and a negative electrode material layer located on at least one surface of the negative electrode current collector. The negative electrode material layer includes a first negative electrode material layer and a second negative electrode material layer. The first negative electrode material layer is located between the negative electrode current collector and the second negative electrode material layer. Both the first negative electrode material layer and the second negative electrode material layer include a silicon-based material. Based on the mass of the negative electrode material layer, the mass percentage content of Si element in the first negative electrode material layer is greater than that in the second negative electrode material layer. The second negative electrode material layer is provided with a plurality of stripes, and the plurality of stripes extend along the width direction after the negative electrode plate is unfolded, and the plurality of stripes are spaced along the length direction after the negative electrode plate is unfolded. By providing stripes on the second negative electrode material layer, the wetting performance of the electrolyte on the negative electrode plate can be improved. The content of Si element in the second negative electrode material layer is relatively low, which is beneficial to reducing the volume expansion of the negative electrode material layer during the cycle. At the same time, by providing stripes on the second negative electrode material layer, the capacity loss of the negative electrode plate is small. Further, the content of Si element in the first negative electrode material layer is relatively high, which is beneficial to improving the capacity of the negative electrode plate. Therefore, the risk of lithium plating caused by insufficient CB value due to the provision of stripes on the second negative electrode material layer can be effectively reduced, thereby improving the cycle performance of the cylindrical secondary battery. While the electrolyte has good wetting performance on the negative electrode plate, the cylindrical secondary battery has good lithium plating performance and cycle performance.

[0007] In one or more embodiments of the present application, along the thickness direction of the negative electrode plate, the thickness of the second negative electrode material layer is D μm, and the depth of a single stripe is d μm. Based on the mass of the second negative electrode material layer, the mass percentage content of Si element in the second negative electrode material layer is W, and the specific capacity of the silicon-based material is C Si mAh / g, 1.01 ≤ W × C Si × d / D ≤ 15.87, preferably 3.20 ≤ W × C Si × d / D ≤ 4.76; 10 ≤ D ≤ 55, preferably 12 ≤ D ≤ 45; 0.6% ≤ W ≤ 5%, preferably 1% ≤ W ≤ 2%; 1300 ≤ C Si ≤ 1800, preferably 1400 ≤ C Si ≤ 1600. By regulating W × C Si × d / D, W, C SiThe values of [parameters related to] D are within the scope of this application, such that the total amount of Si in the second negative electrode material layer is within an appropriate range. When stripes are provided on the second negative electrode material layer, the wettability of the electrolyte to the negative electrode sheet can be improved. At the same time, the capacity loss of the negative electrode sheet is small, and the volume expansion of the negative electrode material layer during the cycling process is relatively uniform, so that the flow rate of the electrolyte in the negative electrode sheet is increased. Thereby, the risk of lithium deposition caused by insufficient CB value due to the provision of stripes in the second negative electrode material layer can be effectively reduced, thus improving the cycling performance of the cylindrical secondary battery.

[0008] In one or more embodiments of this application, along the length direction after the negative electrode sheet is unfolded, the second negative electrode material layer includes a first segment, a second segment, and a third segment connected in sequence. Based on the length of the second negative electrode material layer, the length proportion of the first segment is 10% to 30%, the length proportion of the second segment is 40% to 80%, and the length proportion of the third segment is 10% to 30%. The stripes on the first segment have a first density, the stripes on the second segment have a second density, and the stripes on the third segment have a third density. The second density is greater than the first density, and the third density is less than or equal to the second density. By regulating the magnitude relationship among the first density, the second density, and the third density, the distribution of the electrolyte in the negative electrode sheet is made more uniform, reducing the risk of lithium deposition caused by inconsistent wetting effect of the electrolyte on the negative electrode sheet during the winding process of manufacturing the cylindrical secondary battery, improving the wetting performance of the electrolyte to the negative electrode sheet, and enhancing the cycling performance of the cylindrical secondary battery.

[0009] In one or more embodiments of this application, along the length direction after the negative electrode sheet is unfolded, the number of stripes on the second negative electrode material layer per 2 cm in the first segment is 1 to 3, the number of stripes on the second negative electrode material layer per 2 cm in the second segment is 4 to 6, and the number of stripes on the second negative electrode material layer per 2 cm in the third segment is 2 to 4. By regulating the values of the number of stripes per 2 cm of the second negative electrode material layer in each segment, namely a1, a2, and a3, within the above ranges, the distribution of the electrolyte in the negative electrode sheet is made more uniform, reducing the risk of lithium deposition caused by inconsistent wetting effect of the electrolyte on the negative electrode sheet during the winding process of manufacturing the cylindrical secondary battery, improving the wetting performance of the electrolyte to the negative electrode sheet, and enhancing the cycling performance of the cylindrical secondary battery.

[0010] In one or more embodiments of this application, along the length direction after the negative electrode sheet is unfolded, the width of a single stripe is n μm, where 45 ≤ n ≤ 85. By regulating the width n of a single stripe within the above range, it is beneficial to improve the wetting performance of the electrolyte to the negative electrode sheet, increase the penetration efficiency of the electrolyte to the negative electrode sheet. At the same time, the capacity loss of the negative electrode sheet is small, which is beneficial to reducing the risk of lithium deposition caused by insufficient CB value due to the provision of stripes in the second negative electrode material layer. Therefore, while the electrolyte has good wetting performance to the negative electrode sheet, the cylindrical secondary battery has good lithium deposition resistance performance and cycling performance.

[0011] In one or more embodiments of the present application, along the thickness direction of the negative electrode sheet, the depth of a single stripe is d μm, where 1 ≤ d ≤ 30. By regulating the depth d of a single stripe within the above range, it is beneficial to improve the wetting performance of the electrolyte on the negative electrode sheet, increase the penetration efficiency of the electrolyte into the negative electrode sheet, and at the same time, it is beneficial to reduce the risk of the second negative electrode material layer being punctured by the stripe when setting the stripe. The capacity loss of the negative electrode sheet is small, thereby reducing the risk of lithium deposition caused by insufficient CB value due to setting the stripe in the second negative electrode material layer. Therefore, while the electrolyte has good wetting performance on the negative electrode sheet, the cylindrical secondary battery has good lithium deposition performance and cycling performance.

[0012] In one or more embodiments of the present application, based on the thickness of the negative electrode material layer, the thickness percentage of the second negative electrode material layer is T, where 40% ≤ T ≤ 80%, preferably 50% ≤ T ≤ 75%. By regulating the thickness percentage T of the second negative electrode material layer within the above range, when setting a stripe on the second negative electrode material layer, the risk of the second negative electrode material layer being punctured by the stripe is reduced and the capacity loss of the negative electrode sheet is small, thereby reducing the risk of lithium deposition caused by insufficient CB value due to setting the stripe in the second negative electrode material layer. In addition, while taking into account the capacity of the negative electrode sheet, it is beneficial to inhibit the volume expansion of the first negative electrode material layer during cycling. The volume expansion of the second negative electrode material layer with the stripe is relatively uniform, improving the cycling performance of the secondary battery.

[0013] In one or more embodiments of the present application, based on the mass of Si element in the negative electrode material layer, the mass percentage content of Si element in the second negative electrode material layer is X, where 5% ≤ X ≤ 20%, preferably 8% ≤ X ≤ 15%. Based on the mass of Si element in the negative electrode material layer, by regulating the mass percentage content X of Si element in the second negative electrode material layer within the above range, the content of Si element in the second negative electrode material layer is less, and the volume expansion of the second negative electrode material layer with the stripe is relatively uniform, making the distribution of the electrolyte in the negative electrode sheet relatively uniform, increasing the flow rate of the electrolyte in the negative electrode sheet, thereby improving the cycling performance of the secondary battery; at the same time, when setting a stripe on the second negative electrode material layer, the capacity loss of the negative electrode sheet is small, thereby reducing the risk of lithium deposition caused by insufficient CB value due to setting the stripe in the second negative electrode material layer. Therefore, while the electrolyte has good wetting performance on the negative electrode sheet, the cylindrical secondary battery has good lithium deposition performance and cycling performance.

[0014] The second aspect of the present application provides an electronic device, which includes the cylindrical secondary battery in any of the foregoing embodiments. The cylindrical secondary battery provided by the present application has good lithium deposition performance and cycling performance. Therefore, the electronic device of the present application has a long service life.

[0015] Advantages of the present application:

[0016] In the embodiment of the present application, by providing stripes on the second negative electrode material layer, the wetting performance of the electrolyte on the negative electrode sheet can be improved. The mass percentage content of Si element in the first negative electrode material layer is greater than that in the second negative electrode material layer. The content of Si element in the second negative electrode material layer is relatively low, which is beneficial to reducing the volume expansion of the negative electrode material layer during the cycling process. At the same time, by providing stripes on the second negative electrode material layer, the capacity loss of the negative electrode sheet is small. Further, the content of Si element in the first negative electrode material layer is relatively high, which is beneficial to improving the capacity of the negative electrode sheet. Thus, the risk of lithium deposition caused by insufficient CB value due to the provision of stripes in the second negative electrode material layer can be effectively reduced, thereby improving the cycling performance of the cylindrical secondary battery. While the electrolyte has good wetting performance on the negative electrode sheet, the cylindrical secondary battery has good lithium deposition performance and cycling performance. Description of the Drawings

[0017] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The schematic embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation to the present application.

[0018] Figure 1 It is the front view of the negative electrode sheet in an embodiment of the present application;

[0019] Figure 2 It is Figure 1 the sectional view of the negative electrode sheet in along the A-A direction;

[0020] Figure 3 It is the structural schematic diagram of the negative electrode sheet in an embodiment of the present application;

[0021] Figure 4 It is the front view of the negative electrode sheet in another embodiment of the present application.

[0022] Reference numerals: negative electrode sheet 100; negative electrode current collector 10; negative electrode material layer 20; first negative electrode material layer 21; second negative electrode material layer 22; first section 221; second section 222; third section 223; stripe 30. Detailed Embodiments

[0023] To make the objectives, technical solutions, and advantages of the present application clearer, the following examples are given with reference to the drawings to further elaborate on the present application in detail. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all of them. All other embodiments obtained by those skilled in the art based on the present application fall within the scope of protection of the present application.

[0024] It should be noted that in the description of the invention of the present application, a lithium-ion battery is used as an example of a secondary battery to explain the present application. However, the secondary battery of the present application is not limited to lithium-ion batteries.

[0025] Regarding the problem of electrode sheet wetting caused by the flattened structure of all tab in a cylindrical lithium-ion battery, especially the poor wetting in the middle of the electrode sheet, which in turn affects the performance of the lithium-ion battery. Currently, the following methods are mainly used for improvement: increasing the standing time after injecting the electrolyte during the preparation of the lithium-ion battery to improve the diffusion of the electrolyte, but the production cost increases while the first efficiency of the lithium-ion battery decreases. Or, optimizing the electrolyte composition, such as adding dimethyl carbonate or carboxylic acid ester to the electrolyte to improve the conductivity of the electrolyte. However, during the cycling process of the lithium-ion battery, side reactions will occur between the electrolyte and the positive electrode active material and / or the negative electrode active material, generating excess gas, which is likely to cause safety problems. Furthermore, controlling the porosity of the positive electrode sheet and / or the negative electrode sheet so that the porosity at the edge of the positive electrode sheet and / or the negative electrode sheet is greater than the porosity in the middle. Although the wetting at the edge is improved, the wetting effect in the middle part of the positive electrode sheet and / or the negative electrode sheet decreases, easily leading to the occurrence of electrolyte breakage in the middle part. The inventors have found that setting stripes on the negative electrode sheet can effectively improve the wetting problem of the electrolyte on the negative electrode sheet, but at the same time, it will reduce the capacity of the negative electrode sheet, resulting in insufficient local CB value and lithium deposition on the negative electrode sheet. Especially on the negative electrode sheet containing Si element, the lithium deposition problem is more prominent, and further the cycling performance of the lithium-ion battery decreases. Therefore, the present application provides a secondary battery that can improve the wetting performance of the electrolyte on the negative electrode sheet when the negative electrode sheet contains Si element, thereby improving the cycling performance of the secondary battery.

[0026] The first aspect of the present application provides a cylindrical secondary battery. The cylindrical secondary battery includes a negative electrode plate, and the negative electrode plate includes a negative electrode current collector and a negative electrode material layer located on at least one surface of the negative electrode current collector. The negative electrode material layer includes a first negative electrode material layer and a second negative electrode material layer. The first negative electrode material layer is located between the negative electrode current collector and the second negative electrode material layer. Both the first negative electrode material layer and the second negative electrode material layer include a silicon-based material. Based on the mass of the negative electrode material layer, the mass percentage content of Si element in the first negative electrode material layer is greater than that in the second negative electrode material layer. The second negative electrode material layer is provided with a plurality of stripes, and the plurality of stripes extend along the width direction after the negative electrode plate is unfolded, and the plurality of stripes are spaced along the length direction after the negative electrode plate is unfolded. By providing stripes on the second negative electrode material layer, the wetting performance of the electrolyte on the negative electrode plate can be improved, and the penetration efficiency of the electrolyte on the negative electrode plate can be increased. The negative electrode material layer includes a first negative electrode material layer and a second negative electrode material layer, and the mass percentage content of Si element in the first negative electrode material layer is greater than that in the second negative electrode material layer. The content of Si element in the second negative electrode material layer is relatively low, which is beneficial to reducing the volume expansion of the negative electrode material layer during the cycle. At the same time, stripes are only provided on the second negative electrode material layer, and the capacity loss of the negative electrode plate is small. Further, the content of Si element in the first negative electrode material layer is relatively high, which is beneficial to improving the capacity of the negative electrode plate. Therefore, the risk of lithium deposition caused by insufficient CB value due to the stripes provided on the second negative electrode material layer can be effectively reduced, thereby improving the cycle performance of the cylindrical secondary battery. Thus, while the electrolyte has good wetting performance on the negative electrode plate, the cylindrical secondary battery has good lithium deposition performance and cycle performance.

[0027] In the present application, the CB value refers to the ratio of the capacity of the negative electrode plate per unit area to the capacity of the positive electrode plate under the same conditions. CB = (gram capacity of the negative electrode active material × mass of the negative electrode active material per unit area of the negative electrode plate × mass percentage content of the negative electrode active material in the negative electrode material layer) / (gram capacity of the positive electrode active material × mass of the positive electrode active material per unit area of the positive electrode plate × mass percentage content of the positive electrode active material in the positive electrode material layer). The above unit area refers to 1mm 2. The present application has no particular restriction on the particle size of the silicon-based material. The silicon-based material can be selected from micron-sized silicon-based materials or nano-sized silicon-based materials, as long as the purpose of the present application can be met. For example, the average particle size of the micron-sized silicon-based material can be 3μm to 20μm, and the average particle size of the nano-sized silicon-based material can be 1nm to 100nm. The present application has no particular restriction on the type of silicon-based material, as long as the purpose of the present application can be achieved. For example, the micron-sized silicon-based material includes but is not limited to at least one of micron-sized silicon material, micron-sized silicon-carbon material or micron-sized silicon-oxygen material. The micron-sized silicon material includes micron-sized silicon element, the micron-sized silicon-carbon material includes at least one of micron-sized α-SiC (hexagonal crystal structure) or micron-sized β-SiC (cubic crystal structure), and the micron-sized silicon-oxygen material includes at least one of micron-sized SiO or micron-sized SiO2. Nanoscale silicon-based materials include but are not limited to at least one of nanoscale silicon materials, nanoscale silicon-carbon materials or nanoscale silicon-oxygen materials. Nanoscale silicon materials include nanoscale silicon element. Nanoscale silicon-carbon materials include at least one of nanoscale α-SiC (hexagonal crystal structure) or nanoscale β-SiC (cubic crystal structure). Nanoscale silicon-oxygen materials include at least one of nanoscale SiO or nanoscale SiO2.

[0028] In one embodiment of the present application, along the thickness direction of the negative electrode sheet, the thickness of the second negative electrode material layer is D μm, and the depth of a single stripe is d μm. Based on the mass of the second negative electrode material layer, the mass percentage of Si element in the second negative electrode material layer is W, and the gram capacity of the silicon-based material is C. Si mAh / g, 1.01≤W×C Si ×d / D≤15.87. In some embodiments, 3.20≤W×C Si ×d / D≤4.76. For example, W×C SiThe value of ×d / D can be 1.01, 1.05, 1.1, 1.5, 2, 2.5, 3, 3.2, 3.5, 4, 4.5, 4.76, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10, 10.5, 11, 11.5, 12, 12.5, 13, 13.5, 14, 14.5, 15, 15.5, 15.87 or a range composed of any two of these values. In some embodiments, 10 ≤ D ≤ 55, and in some other embodiments, 12 ≤ D ≤ 45. For example, the value of D can be 10, 12, 15, 17, 20, 22, 25, 27, 30, 32, 35, 37, 40, 42, 45, 47, 50, 52, 55 or a range composed of any two of these values. In some embodiments, 0.6% ≤ W ≤ 5%, and in some other embodiments, 1% ≤ W ≤ 2%. For example, the value of W can be 0.6%, 0.8%, 1%, 1.2%, 1.5%, 1.7%, 2%, 2.2%, 2.5%, 2.7%, 3%, 3.2%, 3.5%, 3.7%, 4%, 4.2%, 4.5%, 4.7%, 5% or a range composed of any two of these values. In some embodiments, 1300 ≤ C Si ≤ 1800, and in some other embodiments, 1400 ≤ C Si ≤ 1600. For example, the value of C Si can be 1300, 1320, 1350, 1370, 1400, 1420, 1450, 1470, 1500, 1520, 1550, 1570, 1600, 1620, 1650, 1670, 1700, 1720, 1750, 1770, 1800 or a range composed of any two of these values.

[0029] In this application, for the convenience of understanding, it is defined that in the unfolded state of the negative electrode tab, its own length direction is the X direction, its own width direction is the Y direction, and its own thickness direction is the Z direction, and a three-dimensional coordinate system is established along the X direction, Y direction, and Z direction. As Figure 1 and Figure 2 shown, along A-A, the cross-section of the negative electrode tab 100 in Figure 1 is obtained, getting Figure 2 . Along the thickness direction (Z direction) of the negative electrode tab 100, the thickness of the second negative electrode material layer 22 is D μm, and the depth of a single stripe 30 is d μm. By regulating W × C SiThe value of ×d / D is within the scope of this application, such that the total amount of Si in the second negative electrode material layer is within a suitable range. When stripes are provided on the second negative electrode material layer, the wettability of the electrolyte on the negative electrode sheet can be improved. At the same time, the capacity loss of the negative electrode sheet is small, and the volume expansion of the negative electrode material layer during the cycling process is relatively uniform, so that the flow rate of the electrolyte in the negative electrode sheet is increased. Thereby, the risk of lithium plating caused by insufficient CB value due to the provision of stripes on the second negative electrode material layer can be effectively reduced, and the cycling performance of the cylindrical secondary battery is thus improved. Controlling the thickness D of the second negative electrode material layer within the above range is beneficial to reducing the risk of the second negative electrode material layer being pierced by the stripes when the stripes are provided, and at the same time can reduce the risk of lithium plating caused by insufficient CB value due to the provision of stripes on the second negative electrode material layer. Controlling the specific capacity C of the silicon-based material Si Within the above range, when stripes are provided on the second negative electrode material layer, the capacity loss of the negative electrode sheet is small, which is beneficial to reducing the risk of lithium plating caused by insufficient CB value due to the provision of stripes on the second negative electrode material layer. Controlling the mass percentage content W of Si element in the second negative electrode material layer within the above range, when stripes are provided on the second negative electrode material layer, the capacity loss of the negative electrode sheet is small, which is beneficial to reducing the risk of lithium plating caused by insufficient CB value due to the provision of stripes on the second negative electrode material layer. At the same time, the volume expansion of the negative electrode material layer during the cycling process is relatively uniform, so that the flow rate of the electrolyte in the negative electrode sheet is increased. Therefore, while the electrolyte has good wettability on the negative electrode sheet, the cylindrical secondary battery has good lithium plating performance and cycling performance. There is no particular limitation on the control method of the specific capacity of the silicon-based material in this application, as long as the object of this application can be achieved. For example, different types of commercially available silicon-based materials can be selected or the average particle size of the same silicon-based material can be adjusted to adjust the specific capacity of the silicon-based material, and combined with the "C Si test" test method in this application to determine the specific capacity of the silicon-based material and select the silicon-based material with the required specific capacity. There is no particular limitation on the control method of the average particle size of the silicon-based material in this application, as long as the object of this application can be achieved. For example, it can be achieved by mechanically crushing and ball milling the particles of the silicon-based material. Generally, for the same silicon-based material, when the ball milling time is extended, the average particle size decreases and the specific capacity of the silicon-based material increases; when the ball milling time is shortened, the average particle size increases and the specific capacity of the silicon-based material decreases. In this application, the average particle size can be understood as the equivalent diameter. The equivalent diameter generally refers to the diameter of a sphere with the same volume as an object with an irregular shape. In this application, by obtaining the negative electrode sheet and measuring the area of the silicon-based material particles to be measured in the cross-section of the negative electrode sheet, and then using the diameter of the circle with the same area as the equivalent diameter of the particles of the silicon-based material to be measured.

[0030] In one embodiment of this application, such as Figure 3As shown, along the length direction (X direction) after the negative electrode tab 100 is unfolded, it can be understood that the length direction (X direction) after the negative electrode tab 100 is unfolded is the same as the winding direction W direction of the negative electrode tab 100 when manufacturing a cylindrical secondary battery. The second negative electrode material layer 22 includes a first section 221, a second section 222, and a third section 223 connected in sequence. It can be understood that when manufacturing a cylindrical secondary battery and during winding of the electrode assembly, the negative electrode tab starts winding from the position where the first section is located. After winding is completed, the first section is located near the winding center of the electrode assembly, and the third section is located away from the winding center of the electrode assembly. Based on the length of the second negative electrode material layer 22, the length proportion of the first section 221 is 10% to 30%, the length proportion of the second section 222 is 40% to 80%, and the length proportion of the third section 223 is 10% to 30%. For example, the length proportion of the first section 221 can be 10%, 12%, 15%, 17%, 20%, 22%, 25%, 27%, 30% or a range composed of any two of these values; the length proportion of the second section 222 can be 40%, 42%, 45%, 47%, 50%, 52%, 55%, 57%, 60%, 62%, 65%, 67%, 70%, 72%, 75%, 77%, 80% or a range composed of any two of these values; the length proportion of the third section 223 can be 10%, 12%, 15%, 17%, 20%, 22%, 25%, 27%, 30% or a range composed of any two of these values. The stripes 30 on the first section 221 have a first density, the stripes 30 on the second section 222 have a second density, and the stripes 30 on the third section 223 have a third density. The second density is greater than the first density, and the third density is less than or equal to the second density. By regulating the magnitude relationship among the first density, the second density, and the third density, the distribution of the electrolyte in the negative electrode tab is made more uniform, reducing the risk of lithium precipitation caused by inconsistent wetting effects of the electrolyte on the negative electrode tab during the process of winding and manufacturing a cylindrical secondary battery, improving the wetting performance of the electrolyte on the negative electrode tab, increasing the wetting efficiency of the electrolyte on the negative electrode tab, and improving the cycling performance of the cylindrical secondary battery. Therefore, while the electrolyte has good wetting performance on the negative electrode tab, the cylindrical secondary battery has good cycling performance. In this application, the first density refers to the number of stripes on the second negative electrode material layer per unit length in the first section, the second density refers to the number of stripes on the second negative electrode material layer per unit length in the second section, and the third density refers to the number of stripes on the third negative electrode material layer per unit length in the third section, where every 2 cm is one unit length.

[0031] In one embodiment of the present application, the number a1 of stripes on the second negative electrode material layer per 2 cm in the first section is 1 to 3, the number a2 of stripes on the second negative electrode material layer per 2 cm in the second section is 4 to 6, and the number a3 of stripes on the second negative electrode material layer per 2 cm in the third section is 2 to 4. For example, the number a1 of stripes on the second negative electrode material layer per 2 cm in the first section may be 1, 2 or 3, the number a2 of stripes on the second negative electrode material layer per 2 cm in the second section is 4, 5 or 6, and the number a3 of stripes on the second negative electrode material layer per 2 cm in the third section may be 2, 3 or 4. By regulating the number of stripes on the second negative electrode material layer of every 2 cm in each section, i.e., the values ​​of a1, a2, and a3, within the above range, the distribution of the electrolyte in the negative electrode sheet is more uniform, reducing the risk of lithium precipitation caused by inconsistent wetting effect of the electrolyte on the negative electrode sheet during the winding process of preparing a cylindrical secondary battery, improving the wetting performance of the electrolyte on the negative electrode sheet, improving the wetting efficiency of the electrolyte on the negative electrode sheet, and improving the cycle performance of the cylindrical secondary battery. Therefore, while the electrolyte has good wetting performance on the negative electrode sheet, the cylindrical secondary battery has good cycle performance. In the present application, the values ​​of the number of stripes on the second negative electrode material layer of every 2 cm in each section, i.e., a1, a2, and a3, are all integers.

[0032] In one embodiment of the present application, Figure 2 As shown, along the length direction (X direction) after the negative electrode sheet 100 is unfolded, the width of a single stripe 30 is nμm, 45≤n≤85. For example, the value of n can be 45, 47, 50, 52, 55, 57, 60, 62, 65, 67, 70, 72, 75, 77, 80, 82, 85 or a range consisting of any two of these values. By regulating the width n of a single stripe within the above range, it is beneficial to improve the wetting performance of the electrolyte on the negative electrode sheet, improve the penetration efficiency of the electrolyte on the negative electrode sheet, and at the same time, the capacity loss of the negative electrode sheet is small, which is beneficial to reduce the risk of lithium precipitation caused by insufficient CB value due to the setting of stripes in the second negative electrode material layer. Therefore, while the electrolyte has good wetting performance on the negative electrode sheet, the cylindrical secondary battery has good lithium precipitation performance and cycle performance. In the present application, the cross section of a single stripe refers to the plane formed by the stripe along the length direction and the thickness direction of the electrode assembly after it is unfolded (or the cross section obtained by sectioning the stripe along the length direction and the thickness direction after the electrode assembly is unfolded). The present application has no special restrictions on the cross-sectional shape of a single stripe, as long as the purpose of the present application can be achieved. For example, the cross section of a single stripe can be a triangle, an arc (the area is smaller than a semicircle with the same radius), a semicircle, a rectangle, a trapezoid or a square. In the present application, the width of a single stripe refers to the maximum size of the cross section of a single stripe along the length direction after the negative electrode sheet is unfolded.

[0033] In an embodiment of the present application, as Figure 2 shown, along the thickness direction (Z direction) of the negative electrode plate 100, the depth of a single stripe 30 is d μm, where 1 ≤ d ≤ 30. For example, the value of d can be 1, 2, 3, 5, 7, 10, 12, 15, 17, 20, 22, 25, 27, 30, or a range composed of any two of these numerical values. By regulating the depth d of a single stripe within the above range, it is beneficial to improve the wetting performance of the electrolyte on the negative electrode plate, increase the penetration efficiency of the electrolyte into the negative electrode plate, and at the same time, it is beneficial to reduce the risk that the second negative electrode material layer is pierced by the stripe when the stripe is set. The capacity loss of the negative electrode plate is small, thereby reducing the risk of lithium deposition caused by insufficient CB value due to setting stripes in the second negative electrode material layer. Therefore, while the electrolyte has good wetting performance on the negative electrode plate, the cylindrical secondary battery has good lithium deposition performance and cycling performance. Among them, along the thickness direction of the negative electrode plate, the depth of a single stripe is less than the thickness of the second negative electrode material layer. In the present application, the depth of a single stripe refers to the distance between the surface of the negative electrode plate and the deepest part of a single stripe along the thickness direction of the negative electrode plate.

[0034] In an embodiment of the present application, based on the thickness of the negative electrode material layer, the thickness ratio of the second negative electrode material layer is T, and 40% ≤ T ≤ 80%. In some embodiments, 50% ≤ T ≤ 75%. For example, the value of T can be 40%, 42%, 45%, 47%, 50%, 52%, 55%, 57%, 60%, 62%, 65%, 67%, 70%, 72%, 75%, 77%, 80% or a range composed of any two of these values. By adjusting the thickness percentage ratio T of the second negative electrode material layer within the above range, when stripes are provided on the second negative electrode material layer, the risk of the second negative electrode material layer being punctured by the stripes is reduced and the capacity loss of the negative electrode plate is small, thereby reducing the risk of lithium plating caused by insufficient CB value due to the provision of stripes on the second negative electrode material layer. In addition, while taking into account the capacity of the negative electrode plate, it is beneficial to inhibit the volume expansion of the first negative electrode material layer during the cycling process. The volume expansion of the second negative electrode material layer with stripes is relatively uniform, improving the cycling performance of the secondary battery. Therefore, while the electrolyte has good wetting performance for the negative electrode plate, the cylindrical secondary battery has good lithium plating performance and cycling performance. In the present application, the thickness percentage ratio of the second negative electrode material layer in the negative electrode material layer can be adjusted by adjusting the thickness of the first negative electrode material layer and / or the thickness of the second negative electrode material layer. In the present application, the thickness of the first negative electrode material layer and the thickness of the second negative electrode material layer can be adjusted by means known to those skilled in the art. For example, when the first negative electrode slurry is coated on the surface of the negative electrode current collector, on the basis that other conditions remain unchanged and the solid content of the first negative electrode slurry is certain, increasing the coating amount of the first negative electrode slurry to increase the thickness of the first negative electrode material layer, and the thickness adjustment method of the second negative electrode material layer can be understood by analogy. The present application does not make special restrictions as long as the purpose of the present application can be achieved.

[0035] In an embodiment of the present application, based on the mass of Si element in the negative electrode material layer, the mass percentage of Si element in the second negative electrode material layer is X, and 5% ≤ X ≤ 20%. In some embodiments, 8% ≤ X ≤ 15%. For example, the value of X can be 5%, 7%, 8%, 10%, 12%, 15%, 17%, 20% or a range composed of any two of these values. Based on the mass of Si element in the negative electrode material layer, by controlling the mass percentage X of Si element in the second negative electrode material layer within the above range, the content of Si element in the second negative electrode material layer is relatively small, which is beneficial to suppressing the volume expansion of the first negative electrode material layer during the cycling process. The volume expansion of the second negative electrode material layer with stripes is relatively uniform, making the electrolyte distribute more uniformly in the negative electrode sheet, increasing the flow rate of the electrolyte in the negative electrode sheet, and thus improving the cycling performance of the secondary battery. At the same time, when stripes are provided on the second negative electrode material layer, the capacity loss of the negative electrode sheet is small, thereby reducing the risk of lithium deposition caused by insufficient CB value due to the provision of stripes on the second negative electrode material layer. Therefore, while the electrolyte has good wetting performance for the negative electrode sheet, the cylindrical secondary battery has good lithium deposition performance and cycling performance.

[0036] In an embodiment of the present application, a plurality of stripes located in the second negative electrode material layer are equally spaced along the length direction after the negative electrode sheet is unfolded. Through the above setting, it is beneficial to improve the operability of setting a plurality of stripes in the second negative electrode material layer, beneficial to improving the wetting performance of the electrolyte for the negative electrode sheet, and improving the cycling performance of the secondary battery while meeting mass production manufacturability.

[0037] The present application does not particularly limit the shape and position of the stripes, as long as the purpose of the present application can be satisfied. For example, along the width direction after the negative electrode sheet is unfolded, the second negative electrode material layer has two opposite edges. The stripe can start from any one of the edges and extend along the width direction of the negative electrode sheet, or the stripe can be located between the two edges. There can also be an included angle between the stripe and the length direction after the negative electrode sheet is unfolded, and the included angle is 30° to 150°. Through the above setting, it is beneficial to improve the wetting performance of the electrolyte for the negative electrode sheet, and improve the cycling performance of the secondary battery while meeting mass production manufacturability. The present application does not particularly limit the length of the stripe, as long as the purpose of the present application can be satisfied. For example, along the width direction after the negative electrode sheet is unfolded, based on the width of the second negative electrode material layer, the length ratio of the stripe can be 60% to 100%. When, along the width direction after the negative electrode sheet is unfolded, based on the width of the second negative electrode material layer, the length ratio of the stripe is 100%, as Figure 4 shown, along the Y direction of the width direction after the negative electrode sheet is unfolded, the length of a single stripe 30 is equal to the width 22 of the second negative electrode material layer. In the present application, the features of the above embodiments can be arbitrarily combined, and the combined embodiments are also within the protection scope of the present application.

[0038] In this application, the "negative electrode material layer located on at least one surface of the negative electrode current collector" means that the negative electrode material layer can be disposed on one surface of the negative electrode current collector along its thickness direction, or can be disposed on both surfaces of the negative electrode current collector along its thickness direction. It should be noted that the "surface" here can be the entire area of the surface of the negative electrode current collector or a partial area of the surface of the negative electrode current collector. This application has no special limitation as long as the purpose of this application can be achieved. This application has no special limitation on the negative electrode current collector as long as the purpose of this application can be achieved. For example, the negative electrode current collector can include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam or composite current collector (such as lithium-copper composite current collector, carbon-copper composite current collector, nickel-copper composite current collector, titanium-copper composite current collector, etc.). In this application, there is no special limitation on the thickness of the negative electrode current collector as long as the purpose of this application can be achieved. For example, the thickness of the negative electrode current collector is 4 μm to 20 μm. The first negative electrode material layer includes, in addition to the silicon-based material, a first negative electrode active material, and the second negative electrode material layer includes, in addition to the silicon-based material, a second negative electrode active material. This application has no special limitation on the types of the first negative electrode active material and the second negative electrode active material as long as the purpose of this application can be achieved. For example, the first negative electrode active material and the second negative electrode active material can each independently be selected from at least one of natural graphite, artificial graphite, mesocarbon microbeads (MCMB), hard carbon or soft carbon. Optionally, the first negative electrode material layer may further include a first conductive agent, a first negative electrode binder and a first dispersant, and the second negative electrode material layer may further include a second conductive agent, a second negative electrode binder and a second dispersant. This application has no special limitation on the types of the first negative electrode binder and the second negative electrode binder as long as the purpose of this application can be achieved. For example, the first negative electrode binder and the second negative electrode binder can include, but are not limited to, at least one of polyvinylidene fluoride, copolymer of vinylidene fluoride-hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate salt, polyvinylpyrrolidone, polyethylene ether, polymethyl methacrylate, polytetrafluoroethylene or polyhexafluoropropylene. This application has no special limitation on the types of the first conductive agent and the second conductive agent as long as the purpose of this application can be achieved. For example, the first conductive agent and the second conductive agent can include, but are not limited to, at least one of conductive carbon black (Super P), carbon nanotubes (CNTs), carbon fiber, flake graphite, Ketjen black, graphene, metal material or conductive polymer. The above carbon nanotubes can include, but are not limited to, single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above carbon fiber can include, but are not limited to, vapor-grown carbon fiber (VGCF) and / or nanofiber. The above metal material can include, but are not limited to, metal powder and / or metal fiber. Specifically, the metal can include, but is not limited to, at least one of copper, nickel, aluminum or silver. The above conductive polymer can include, but is not limited to, at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene or polypyrrole.The first dispersant and the second dispersant may include, but are not limited to, carboxymethyl cellulose or sodium carboxymethyl cellulose.

[0039] The present application does not particularly limit the method for preparing the negative electrode sheet, as long as the purpose of the present application can be achieved. For example, the method for preparing the negative electrode sheet includes, but is not limited to, the following steps: (1) uniformly mixing a mixture of a first negative electrode active material and a silicon-based material, a first negative electrode binder, a first conductive agent, and a first dispersant to obtain a first negative electrode slurry, and uniformly mixing a mixture of a second negative electrode active material and a silicon-based material, a second negative electrode binder, a second conductive agent, and a second dispersant to obtain a second negative electrode slurry; (2) coating the first negative electrode slurry on one surface of the negative electrode current collector, and after drying, obtaining a negative electrode sheet coated with a first negative electrode material layer, coating the second negative electrode slurry on the surface of the first negative electrode material layer away from the negative electrode current collector, and after drying, obtaining a negative electrode sheet with a first negative electrode material layer and a second negative electrode material layer coated on one side; (3) repeating the above operations on the other surface of the negative electrode current collector to obtain a negative electrode sheet with a first negative electrode material layer and a second negative electrode material layer coated on both sides; (4) after cold pressing and slitting, sequentially arranging corresponding numbers of stripes in the first section, the second section, and the third section of the second negative electrode material layer along the length direction of the negative electrode sheet to obtain the negative electrode sheet.

[0040] There is no particular limitation on the solid content of the first negative electrode slurry and the second negative electrode slurry in the above step (1) of the present application, as long as the purpose of the present application can be achieved. There is no particular limitation on the drying time and temperature in the above step (2) of the present application, as long as the purpose of the present application can be achieved. There is no particular limitation on the process parameters of cold pressing in the above step (4) of the present application, as long as the purpose of the present application can be achieved. There is no particular limitation on the method of setting stripes in the above step (4) of the present application, as long as the purpose of the present application can be achieved. For example, stripes can be set by means of pulsed laser etching. The depth d of a single stripe and the width n of a single stripe can be regulated by the power and defocus amount of the pulsed laser emitter, and the distance between adjacent stripes can be regulated by adjusting the spacing between pulsed laser emitters. Among them, when the first negative electrode slurry and the second negative electrode slurry are coated on one surface of the negative electrode current collector, the stripes are only set on one surface of the negative electrode plate; when the first negative electrode slurry and the second negative electrode slurry are coated on two surfaces of the negative electrode current collector, the stripes are respectively set on two surfaces of the negative electrode plate. There is no particular limitation on regulating the values of D and T in the present application, as long as the purpose of the present application can be achieved. For example, the values of D and T can be regulated by adjusting the coating amount of the negative electrode material layer. When the coating amount of the first negative electrode material layer is constant, increasing the coating amount of the second negative electrode material layer, the value of D becomes larger and the value of T becomes larger; decreasing the coating amount of the second negative electrode material layer, the value of D becomes smaller and the value of T becomes smaller. There is no particular limitation on regulating the values of W and X in the present application, as long as the purpose of the present application can be achieved. For example, the values of W and X can be regulated by adjusting the proportion of the silicon-based material in the mixture of the second negative electrode active material and the silicon-based material. When the proportion of the silicon-based material in the mixture of the first negative electrode active material and the silicon-based material is constant, increasing the proportion of the silicon-based material in the mixture of the second negative electrode active material and the silicon-based material, the value of W becomes larger and the value of X becomes larger; decreasing the proportion of the silicon-based material in the mixture of the second negative electrode active material and the silicon-based material, the value of W becomes smaller and the value of X becomes smaller.

[0041] In the present application, the cylindrical secondary battery includes a positive electrode tab. There is no particular limitation on the positive electrode tab in the present application, as long as the object of the present application can be achieved. For example, the positive electrode tab includes a positive electrode current collector and a positive electrode material layer provided on at least one surface of the positive electrode current collector. The above-mentioned "positive electrode material layer provided on at least one surface of the positive electrode current collector" means that the positive electrode material layer can be provided on one surface of the positive electrode current collector along its own thickness direction, or can be provided on both surfaces of the positive electrode current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of the surface of the positive electrode current collector, or can be a partial area of the surface of the positive electrode current collector. There is no particular limitation in the present application, as long as the object of the present application can be achieved. There is no particular limitation on the positive electrode current collector in the present application, as long as the object of the present application can be achieved. For example, the positive electrode current collector can include aluminum foil, aluminum alloy foil, or a composite current collector (such as an aluminum-carbon composite current collector), etc. The positive electrode material layer of the present application includes a positive electrode active material. There is no particular limitation on the type of the positive electrode active material in the present application, as long as the object of the present application can be achieved. For example, the positive electrode active material can include at least one of lithium nickel cobalt manganese oxide (NCM811, NCM622, NCM523, NCM111), lithium nickel cobalt aluminate, lithium iron phosphate, lithium-rich manganese-based material, lithium cobalt oxide (LiCoO2), lithium manganese oxide, lithium manganese iron phosphate, or lithium titanate, etc. In the present application, the positive electrode active material can also include a non-metallic element. For example, the non-metallic element includes at least one of fluorine, phosphorus, boron, chlorine, silicon, or sulfur. In the present application, there is no particular limitation on the thickness of the positive electrode current collector and the positive electrode material layer, as long as the object of the present application can be achieved. For example, the thickness of the positive electrode current collector is 5 μm to 20 μm, preferably 6 μm to 18 μm. The thickness of the single-sided positive electrode material layer is 30 μm to 120 μm. In the present application, the positive electrode material layer can also include a positive electrode binder and a conductive agent. There is no particular limitation on the type of the positive electrode binder in the positive electrode material layer in the present application, as long as the object of the present application can be achieved. For example, the positive electrode binder can be of the same type as the negative electrode binder in the above-mentioned first negative electrode material layer and second negative electrode material layer. There is no particular limitation on the type of the conductive agent in the positive electrode material layer in the present application, as long as the object of the present application can be achieved. For example, the conductive agent can be of the same type as the conductive agent in the above-mentioned first negative electrode material layer and second negative electrode material layer. There is no particular limitation on the mass ratio of the positive electrode active material, positive electrode binder, and conductive agent in the positive electrode material layer. Those skilled in the art can select according to actual needs, as long as the object of the present application can be achieved.

[0042] This application has no special restrictions on the separator, as long as the purpose of this application can be achieved. For example, the materials of the separator may include, but are not limited to, at least one of polyolefins (PO) mainly composed of polyethylene (PE) and polypropylene (PP), polyesters (such as polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex or aramid. The types of separators may include at least one of woven membranes, non-woven membranes, microporous membranes, composite membranes, rolled membranes or spun membranes. The separator of this application may have a porous structure, and this application has no special restrictions on the size of the pore diameter of the porous structure of the separator, as long as the purpose of this application can be achieved. For example, the size of the pore diameter may be 0.01 μm to 1 μm. This application has no special restrictions on the thickness of the separator, as long as the purpose of this application can be achieved. For example, the thickness of the separator may be 5 μm to 50 μm.

[0043] The cylindrical secondary battery of the present application includes an electrolyte, and the electrolyte includes a lithium salt and a non-aqueous solvent. The lithium salt may include at least one of LiPF6, LiNO3, LiBF4, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, Li2SiF6, lithium bis(oxalato)borate (LiBOB), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), or lithium difluoroborate. The present application does not limit the content of the lithium salt in the electrolyte, as long as the object of the present application can be achieved. The present application does not particularly limit the non-aqueous solvent, as long as the object of the present application can be achieved. For example, the non-aqueous solvent may include, but is not limited to, at least one of carbonate compounds, carboxylate compounds, ether compounds, or other organic solvents. The above carbonate compounds may include, but are not limited to, at least one of linear carbonate compounds, cyclic carbonate compounds, or fluorinated carbonate compounds. The above linear carbonate compounds may include, but are not limited to, at least one of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, or methyl ethyl carbonate. The above cyclic carbonates may include, but are not limited to, at least one of ethylene carbonate, propylene carbonate (PC), butylene carbonate, or vinylene carbonate. The fluorinated carbonate compound may include, but is not limited to, at least one of fluorinated ethylene carbonate, 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, or trifluoromethyl ethylene carbonate. The above carboxylate compounds may include, but are not limited to, at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanolide, valerolactone, or caprolactone. The above ether compounds may include, but are not limited to, at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran, or tetrahydrofuran. The above other organic solvents may include, but are not limited to, at least one of dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, or trioctyl phosphate.

[0044] The cylindrical secondary battery of the present application further includes a housing for accommodating the positive electrode sheet, the negative electrode sheet, the separator, and the electrolyte, as well as other components known in the art in the cylindrical secondary battery. The present application does not limit the above-mentioned other components. The present application has no particular limitation on the housing, and it can be a housing well-known in the art as long as the purpose of the present application can be achieved.

[0045] There is no particular limitation on the cylindrical secondary battery of the present application, and it can include any device that generates an electrochemical reaction. In one embodiment of the present application, the cylindrical secondary battery may include, but is not limited to: lithium ion secondary battery (lithium ion battery), lithium polymer secondary battery, or lithium ion polymer secondary battery, etc.

[0046] There is no particular limitation on the preparation method of the cylindrical secondary battery of the present application, and a preparation method well-known in the art can be selected as long as the purpose of the present application can be achieved. For example, the preparation method of the cylindrical secondary battery includes, but is not limited to, the following steps: stacking the separator, the positive electrode sheet, the separator, and the negative electrode sheet in sequence, and performing operations such as winding and folding as needed to obtain a wound electrode assembly, placing the electrode assembly into the housing, injecting the electrolyte into the housing and sealing it to obtain the cylindrical secondary battery.

[0047] The second aspect of the present application provides an electronic device, which includes the cylindrical secondary battery in any of the foregoing embodiments. The cylindrical secondary battery provided by the present application has good lithium deposition performance and cycling performance. Therefore, the electronic device of the present application has a long service life.

[0048] There is no particular limitation on the electronic device of the present application, and it can be any electronic device known in the prior art. For example, the electronic device may include, but is not limited to, a notebook computer, a pen input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, a liquid crystal TV, a portable cleaner, a portable CD player, a mini disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, an automobile, a motorcycle, a moped, a bicycle, a lighting fixture, a toy, a game console, a clock, a power tool, a flash, a camera, a large household battery, and a lithium ion capacitor.

[0049] Examples

[0050] Hereinafter, examples and comparative examples are given to illustrate the embodiments of the present application more specifically. Various tests and evaluations are carried out according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.

[0051] Test methods and equipment:

[0052] At an ambient temperature of 25 °C, the lithium-ion battery was disassembled, the negative electrode sheet was taken out, soaked in dimethyl carbonate (DMC) for 20 min, and then the negative electrode sheet was placed in an oven and dried at 80 °C for 12 h to obtain a negative electrode sheet sample. For the following C Si tests, the negative electrode sheet samples in the tests of the average particle size of the silicon-based material particles and the tests of D, d, T, W, X, and n were all sampled by the above method.

[0053] C Si tests:

[0054] The tested negative electrode sheet was weighed to obtain the mass M of the negative electrode sheet. A copper foil of the same area was weighed to obtain the mass m of the negative electrode current collector copper foil. The mass of the tested negative electrode material layer was M - m. The tested negative electrode sheet was used as the working electrode, and the lithium sheet was used as the counter electrode. The separator was placed between the tested negative electrode sheet and the lithium sheet to play a role of isolation. The electrolyte was injected, and a button cell was assembled. A Blue Power tester was used for testing, and the voltage, capacity, and current of the button cell during the test were recorded: (1) Stand still for 3 h; (2) Discharge at 0.05C direct current to 0.005 V, and then discharge at 50 μA direct current again to 0.005 V; (3) Stand still for 5 min; (4) Charge at 0.05C constant current to 2 V; (5) Stand still for 5 min; (6) Steps (2) to (5) were cycled 2 times (cls); End. The capacity after the end of the second cycle was taken as the capacity C0 of the button cell. The specific capacity of the tested negative electrode material layer was calculated as C0 / (M - m). Among them, the separator and electrolyte used in the test were the same as those in Example 1-1.

[0055] As Figure 1 Prepare the cross-section of the negative electrode sheet 100 along A-A, and perform ion polishing treatment on the cross-section of the negative electrode sheet 100 along A-A to obtain as Figure 2Cross-section of the negative electrode sheet 100. The cross-section of the negative electrode sheet 100 was observed using a scanning electron microscope, and then the silicon-based material and graphite particles in the negative electrode material layer 20 of the cross-section of the negative electrode sheet 100 were distinguished and counted through the backscattering mode to obtain the proportion a1 of graphite particles in the negative electrode material layer 20 and the proportion b1 of the silicon-based material in the negative electrode material layer 20. Among them, due to the higher atomic number and higher electron density of the silicon-based material, and the stronger interaction between the silicon-based material and the test electron beam compared with the interaction between the graphite particles and the test electron beam, the silicon-based material region is brighter, and similarly, the graphite particle region is darker. And an energy-dispersive X-ray spectrometer (EDS) was used to perform elemental analysis tests on the negative electrode material layer 20 in the cross-section of the negative electrode sheet 100. The energy-dispersive X-ray spectrometer (EDS) was used to distinguish C material and Si material to determine the proportion a2 of graphite particles in the negative electrode material layer 20 and the proportion b2 of the silicon-based material in the negative electrode material layer 20. The proportion a of graphite particles in the negative electrode material layer 20 = (a1 + a2) / 2, and the proportion b of the silicon-based material in the negative electrode material layer 20 = (b1 + b2) / 2. According to the specific capacity C0 / (M - m) of the measured negative electrode material layer 20, the proportion of the silicon-based material in the negative electrode material layer 20, and the specific capacity (360 mAh / g) of the graphite particles, C Si = C0 / (M - m) - 360a / b, the specific capacity C of the silicon-based material was obtained Si .

[0056] Measurement of the average particle size of the silicon-based material:

[0057] The average particle size of the silicon-based material was measured using a scanning electron microscope (SEM). As Figure 1 Prepare the cross-section of the negative electrode sheet 100 along A-A, and perform ion polishing treatment on the cross-section of the negative electrode sheet 100 along A-A to obtain the cross-section of the negative electrode sheet 100 as Figure 2 . The cross-section of the negative electrode sheet 100 was observed using a scanning electron microscope, and then the silicon-based material and graphite particles in the negative electrode material layer 20 of the cross-section of the negative electrode sheet 100 were distinguished through the backscattering mode. Randomly select 32 silicon-based material particles to measure their equivalent diameters, and the average value is the measured average particle size of the silicon-based material. In this application, the average particle size can be understood as the equivalent diameter. The equivalent diameter usually refers to the diameter of a sphere with the same volume as an object with an irregular shape. By measuring the area of the particles of the silicon-based material to be measured in the cross-section of the negative electrode sheet, and then using the diameter of the circle with the same area as the area as the equivalent diameter of the particles of the silicon-based material to be measured

[0058] Measurement of D, d, T, W, X, and n:

[0059] As Figure 1 Prepare the cross-section of the negative electrode sheet 100 along A-A, and perform ion polishing treatment on the cross-section of the negative electrode sheet 100 along A-A to obtain the cross-section asFigure 2 Cross-section of the negative electrode plate 100. Using a scanning electron microscope to observe the cross-section of the negative electrode plate 100, a relatively clear double-layer coating boundary line, the boundary line between the first negative electrode material layer 21 and the negative electrode current collector 10, and the cross-sectional shape of the stripe 30 can be observed. Measure the maximum length between the cross-sections of individual stripes 30 along the length direction after the negative electrode plate 100 is unfolded, which is the width n of a single stripe 30. Determine the positions of the first negative electrode material layer 21, the second negative electrode material layer 22, and the negative electrode current collector 10 through the two boundary lines. Along the thickness direction (Z direction) of the negative electrode plate 100, measure the distance from the surface of the negative electrode plate 100 to the double-layer coating boundary line, which is the thickness D of the second negative electrode material layer 22. The distance from the surface of the negative electrode plate 100 to the deepest part of a single stripe 30 is the depth d of a single stripe 30. The distance from the surface of the negative electrode plate 100 to the boundary line between the negative electrode material layer 20 and the negative electrode current collector 10 is the thickness of the negative electrode material layer 20. The ratio of the thickness D of the second negative electrode material layer 22 to the thickness of the negative electrode material layer 20 is the thickness ratio T of the second negative electrode material layer 22.

[0060] Using an energy dispersive spectrometer (EDS) to perform elemental analysis tests on the negative electrode material layer 20, the first negative electrode material layer 21, and the second negative electrode material layer 22 in the cross-section of the negative electrode plate 100 respectively. Calculate the mass percentage W of Si element in the second negative electrode material layer 22 based on the mass of the second negative electrode material layer 22, and the mass percentage X of Si element in the second negative electrode material layer 22 based on the mass of Si element in the negative electrode material layer 20.

[0061] Lithium plating performance test:

[0062] Place the lithium-ion batteries in the examples and comparative examples in an incubator at 10°C. After 60 minutes, charge them at a constant current of 2C to 4.2V, then charge them at a constant voltage of 4.2V until the current is 0.05C. After standing for 5 minutes, discharge them at a constant current of 0.5C to 2.5V. This is one cycle. After cycling 10 times according to the above charge-discharge process, then charge them at a constant current of 2C to 4.2V, disassemble the lithium-ion battery, and observe the lithium plating state on the surface of the negative electrode plate. The non-lithium-plated area on the surface of the negative electrode plate is golden yellow, and the lithium-plated area is grayish white.

[0063] The judgment criteria for the lithium plating degree of lithium-ion batteries are as follows: The lithium plating area of 0% means no lithium plating, the lithium plating area greater than 0 and less than or equal to 2% means mild lithium plating, the lithium plating area greater than 2% and less than or equal to 20% means moderate lithium plating, and the lithium plating area greater than 20% and less than or equal to 100% means severe lithium plating, where the percentage of the lithium plating area is calculated based on the total area of the negative electrode material layer.

[0064] Cycle performance test:

[0065] The lithium-ion batteries in the examples and comparative examples were subjected to charge-discharge cycle tests in a 25 °C constant temperature oven. The lithium-ion batteries were charged at a constant current of 2C to 4.2V, charged at a constant voltage of 4.2V to 0.05C, allowed to stand for 5 minutes, and then discharged at a constant current of 6C to 2.5V. This was the first cycle, and the initial discharge capacity C1 was recorded. After cycling 600 times according to the above cycle process, the discharge capacity C of the lithium-ion battery was recorded. 600 The cycle capacity retention rate at the 600th cycle was calculated as an index to evaluate the wetting effect of the negative electrode sheet and the cycle performance of the lithium-ion battery, and the formula is shown in Equation (I). When the capacity retention rate at 600 cycles (cls) is lower, it indicates that the wetting effect of the negative electrode sheet in the lithium-ion battery is worse, and the cycle performance of the lithium-ion battery is worse; when the capacity retention rate at 600 cls is higher, it indicates that the wetting effect of the negative electrode sheet in the lithium-ion battery is better, and the cycle performance of the lithium-ion battery is better.

[0066] Capacity retention rate at 600 cls (%) = C 600 / C1 × 100%. (I)

[0067] Example 1-1

[0068] <Preparation of negative electrode sheet>

[0069] A mixture of the first negative electrode active material natural graphite and the silicon-based material nano-SiO, the first dispersant sodium carboxymethylcellulose, and the first negative electrode binder styrene-butadiene rubber was mixed in a mass ratio of 97.3:1.7:1.0, and then deionized water was added as a solvent and stirred and mixed evenly to obtain a first negative electrode slurry with a solid content of 50 wt%. A mixture of the second negative electrode active material natural graphite and the silicon-based material nano-SiO, the second dispersant sodium carboxymethylcellulose, and the second negative electrode binder styrene-butadiene rubber was mixed in a mass ratio of 97.3:1.7:1.0, and then deionized water was added as a solvent and stirred and mixed evenly to obtain a second negative electrode slurry with a solid content of 50 wt%. The first negative electrode slurry was uniformly coated on one surface of the negative electrode current collector copper foil and dried at 105 °C. The second negative electrode slurry was uniformly coated on the surface of the first negative electrode material layer away from the negative electrode current collector copper foil and dried at 105 °C to obtain a negative electrode sheet with a single-sided coating of the first negative electrode material layer and the second negative electrode material layer. Then, the above steps were repeated on the other surface of the negative electrode current collector copper foil to obtain a negative electrode sheet with a double-sided coating of the first negative electrode material layer and the second negative electrode material layer. Then, after cold pressing and slitting, the end of the second negative electrode material layer was determined when making a cylindrical lithium-ion battery.

[0070] Starting from the end of the second negative electrode material layer, along the length direction of the negative electrode plate, determine the first section, the second section, and the third section of the second negative electrode material layer. Based on the length of the second negative electrode material layer, the length ratio of the first section is 30%, the length ratio of the second section is 40%, and the length ratio of the third section is 30%. The number of stripes a1 on the second negative electrode material layer per 2 cm in the first section is 2; the number of stripes a2 on the second negative electrode material layer per 2 cm in the second section is 5; the number of stripes a3 on the second negative electrode material layer per 2 cm in the third section is 3.

[0071] As Figure 2 shown, a cross-sectional view is taken along the length direction (X direction) and the thickness direction (Z direction) after the negative electrode plate 100 is unfolded. The cross-sectional shape of a single stripe 30 is arc-shaped. The depth d of a single stripe 30 is 5.33 μm, and the width n of a single stripe 30 is 65 μm. According to the above data, laser-etched stripes are made on the first section, the second section, and the third section on the surfaces of the two second negative electrode material layers of the negative electrode plate, and a negative electrode plate with a specification of 62 mm × 1464 mm is obtained. Among them, based on the mass of the first negative electrode material layer, the mass percentage content of Si element is 5.8%; based on the mass of the second negative electrode material layer, the mass percentage content W of Si element is 0.8%. Based on the mass of Si element in the negative electrode material layer, the mass percentage content X of Si element in the second negative electrode material layer is 12%. The specific capacity C Si of the silicon-based material nano-SiO is 1500 mAh / g. The average particle size of the silicon-based material nano-SiO is 75 nm, the ball milling time is 6 h, the thickness D of the second negative electrode material layer is 20 μm, and based on the thickness of the negative electrode material layer, the thickness ratio T of the second negative electrode material layer is 60%.

[0072] <Preparation of the positive electrode plate>

[0073] Disperse the positive electrode active material lithium nickel cobalt manganate (LiNi 0.8 Co 0.1 Mn 0.1 O2), the binder polyvinylidene fluoride (PVDF), and conductive carbon black in a mass ratio of 94.8:2.8:2.4 in an N-methylpyrrolidone (NMP) solvent, stir and mix well to obtain a positive electrode slurry with a solid content of 72 wt%. Uniformly coat the positive electrode slurry on one surface of a positive electrode current collector aluminum foil with a thickness of 13 μm, and dry it at 105°C to obtain a positive electrode plate with a single-sided coated positive electrode material layer. Then, repeat the above steps on the other surface of the positive electrode current collector aluminum foil to obtain a positive electrode plate with a double-sided coated positive electrode material layer. Then, after cold pressing, slicing, and slitting, dry it in a vacuum at 105°C for 4 h to obtain a positive electrode plate with a specification of 60.3 mm × 1400 mm for use. Among them, the coating weight of the positive electrode material layer is 12 mg / cm 2, the tap density of the positive electrode material layer is 3.4 g / cm 3 .

[0074] <Preparation of Separator>

[0075] A polyethylene (PE) film with a thickness of 12 μm is used as the separator.

[0076] <Preparation of Electrolyte>

[0077] In a dry argon atmosphere glove box, the organic solvents ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a mass ratio of 30:50:20, and then the lithium salt lithium hexafluorophosphate (LiPF6) is added to the above organic solvents. After thorough mixing, the electrolyte is obtained. Based on the mass of the electrolyte, the mass percentage content of LiPF6 is 12.5%.

[0078] <Preparation of Lithium-Ion Battery>

[0079] The separator, positive electrode sheet, separator, and negative electrode sheet prepared above are stacked in sequence, with the separator placed between the positive electrode and the negative electrode to play an insulating role. After winding, flattening, current collector welding, casing insertion, inkjet coding, vacuum drying, electrolyte injection, crimping, and high-temperature standing, formation capacity is carried out, and then a cylindrical lithium-ion battery can be obtained. Among them, during winding, winding is carried out from the position where the first section is located. After winding is completed, the first section is located near the winding center of the electrode assembly, and the third section is located far from the winding center of the electrode assembly. The upper limit voltage for formation is 3.6 V, the formation temperature is 45 °C, and the formation standing time is 2 h.

[0080] Examples 1-2 to 1-28

[0081] Except for adjusting the preparation parameters according to Table 1, the rest are the same as Example 1-1. Among them, when D and W change, the coating amounts of the first negative electrode material layer and the second negative electrode material layer, and the proportions of the silicon-based material in the mixture of the first negative electrode active material and the silicon-based material and in the mixture of the second negative electrode active material and the silicon-based material are adjusted so that the values of D and W are as shown in Table 1.

[0082] Examples 1-29 to Examples 1-34

[0083] Except for adjusting the preparation parameters according to Table 1, the rest are the same as Example 1-14. Among them, when the average particle size of the silicon-based material particles changes, the ball milling time is adjusted so that the average particle size of the silicon-based material particles is as shown in Table 1.

[0084] Example 1-35

[0085] Except for replacing the nano - SiO of the silicon - based material with micron - sized SiO and adjusting the preparation parameters according to Table 1, the rest is the same as in Examples 1 - 14. Among them, the average particle size of the micron - sized SiO is 12 μm, that is, 12000 nm.

[0086] Examples 1 - 36

[0087] Except for replacing the nano - SiO of the silicon - based material with nano - Si and adjusting the relevant parameters according to Table 1, the rest is the same as in Examples 1 - 34.

[0088] Examples 1 - 37 to Examples 1 - 53

[0089] Except for adjusting the preparation parameters according to Table 1, the rest is the same as in Example 1 - 1. Among them, when T and X change, adjust the coating amounts of the first negative electrode material layer, the second negative electrode material layer, the proportion of the silicon - based material in the mixture of the first negative electrode active material and the silicon - based material, and the proportion of the silicon - based material in the mixture of the second negative electrode active material and the silicon - based material so that the values of T and X are as shown in Table 1. When the average particle size of the silicon - based material particles changes, adjust the ball - milling time so that the average particle size of the silicon - based material particles is as shown in Table 1.

[0090] Examples 2 - 1 to Examples 2 - 8

[0091] Except for adjusting the preparation parameters according to Table 2, the rest is the same as in Example 1 - 1.

[0092] Comparative Example 1

[0093] Except for not setting stripes on the second negative electrode material layer, the rest is the same as in Example 1 - 1.

[0094] Comparative Example 2

[0095] Except for preparing the negative electrode sheet by the following steps, the rest is the same as in Example 1 - 1.

[0096] <Preparation of the negative electrode sheet>

[0097] A mixture of natural graphite as the negative electrode active material and nano - SiO as the silicon - based material, sodium carboxymethyl cellulose as the dispersant, and styrene - butadiene rubber as the negative electrode binder are mixed in a mass ratio of 97.3:1.7:1.0. Then, deionized water is added as a solvent and stirred evenly to obtain a negative electrode slurry with a solid content of 50 wt%. The negative electrode slurry is evenly coated on one surface of the negative electrode current collector copper foil and dried at 105 °C to obtain a negative electrode sheet with a single - sided coated negative electrode material layer. Then, the above steps are repeated on the other surface of the negative electrode current collector copper foil to obtain a negative electrode sheet with a double - sided coated negative electrode material layer. Then, after cold pressing and slitting, laser etching stripes are made on the surfaces of the two negative electrode material layers of the negative electrode sheet along the length direction of the negative electrode sheet. The number of stripes on each 2 - cm negative electrode material layer is 2, and a negative electrode sheet with a specification of 62 mm×1464 mm is obtained. Among them, the cross - sectional shape of a single stripe is arc - shaped. Along the thickness direction of the negative electrode sheet, the depth d of a single stripe is 5.33 μm. Along the length direction after the negative electrode sheet is unfolded, the width n of a single stripe is 65 μm. Based on the mass of the negative electrode material layer, the mass percentage content of Si element is 5.8%, the specific capacity C of the nano - SiO silicon - based material Si is 1500 mAh / g, the average particle size of the nano - SiO silicon - based material is 75 nm, and the thickness of the negative electrode material layer is 33.3 μm.

[0098] Comparative Example 3

[0099] Except for preparing the negative electrode sheet by the following steps, the rest is the same as in Example 1 - 1.

[0100] <Preparation of Negative Electrode Sheet>

[0101] A mixture of natural graphite as the negative electrode active material and nano - SiO as the silicon - based material, sodium carboxymethyl cellulose as the dispersant, and styrene - butadiene rubber as the negative electrode binder are mixed in a mass ratio of 97.3:1.7:1.0. Then, deionized water is added as a solvent and stirred evenly to obtain a negative electrode slurry with a solid content of 50 wt%. The negative electrode slurry is evenly coated on one surface of the negative electrode current collector copper foil and dried at 105 °C to obtain a negative electrode sheet with a single - sided coated negative electrode material layer. Then, the above steps are repeated on the other surface of the negative electrode current collector copper foil to obtain a negative electrode sheet with a double - sided coated negative electrode material layer. Then, after cold pressing and slitting, laser etching stripes are made on the surfaces of the two negative electrode material layers of the negative electrode sheet along the length direction of the negative electrode sheet. The number of stripes on each 2 - cm negative electrode material layer is 2, and a negative electrode sheet with a specification of 62 mm×1464 mm is obtained. Among them, the cross - sectional shape of a single stripe is arc - shaped. Along the thickness direction of the negative electrode sheet, the depth d of a single stripe is 5.33 μm. Along the length direction after the negative electrode sheet is unfolded, the width n of a single stripe is 65 μm. Based on the mass of the negative electrode material layer, the mass percentage content of Si element is 0.8%, the specific capacity C of the nano - SiO silicon - based materialSi is 1500 mAh / g, the average particle size of the silicon-based material nano-SiO is 75 nm, and the thickness of the negative electrode material layer is 33.3 μm.

[0102] Comparative Example 4

[0103] Except for preparing the negative electrode plate by the following steps, the rest is the same as in Example 1-1.

[0104] <Preparation of Negative Electrode Plate>

[0105] Mix the mixture of the negative electrode active material natural graphite and the silicon-based material nano-SiO, the dispersant sodium carboxymethylcellulose, and the negative electrode binder styrene-butadiene rubber according to a mass ratio of 97.3:1.7:1.0, then add deionized water as a solvent, stir and mix evenly to obtain a negative electrode slurry with a solid content of 50 wt%. Coat the negative electrode slurry evenly on one surface of the negative electrode current collector copper foil, dry it at 105 °C to obtain a negative electrode plate with a single-sided coated negative electrode material layer. Then repeat the above steps on the other surface of the negative electrode current collector copper foil to obtain a negative electrode plate with a double-sided coated negative electrode material layer. Then, after cold pressing and slitting, a negative electrode plate with a specification of 62 mm × 1464 mm is obtained. Among them, based on the mass of the negative electrode material layer, the mass percentage content of Si element is 5.8%, and the specific capacity C of the silicon-based material nano-SiO Si is 1500 mAh / g, the average particle size of the silicon-based material nano-SiO is 75 nm, and the thickness of the negative electrode material layer is 33.3 μm.

[0106] Comparative Example 5

[0107] Except for swapping the positions of the first negative electrode material layer and the second negative electrode material layer, the rest is the same as in Example 1-1.

[0108] The preparation parameters and performance parameters of each example and comparative example are shown in Tables 1 to 2.

[0109] Table 1

[0110]

[0111]

[0112]

[0113] Note: " / " in Table 1 indicates no relevant preparation parameters.

[0114] It can be seen from Examples 1-1 to 1-53 and Comparative Examples 1 to 5 that by controlling the mass percentage content of Si element in the first negative electrode material layer to be greater than that in the second negative electrode material layer and providing stripes on the second negative electrode material layer, the degree of lithium plating of the lithium-ion battery is lighter, and the 600cls capacity retention rate of the lithium-ion battery is improved, indicating that the electrolyte has a good wetting effect on the negative electrode sheet of the present application, and the lithium-ion battery has good lithium plating performance and cycling performance. In Comparative Example 1, no stripes are provided on the second negative electrode material layer. In Comparative Examples 2 and 3, there is only one negative electrode material layer on each side of the negative electrode current collector of the lithium-ion battery. In Comparative Example 4, there is only one negative electrode material layer on each side of the negative electrode current collector of the lithium-ion battery, and no stripes are provided on the negative electrode material layer. In the lithium-ion battery of Comparative Example 5, the mass percentage content of Si element in the first negative electrode material layer is less than that in the second negative electrode material layer. The degree of lithium plating of the lithium-ion batteries in Comparative Examples 1 to 5 is heavier and the 600cls capacity retention rate is lower. While the degree of lithium plating of the lithium-ion batteries in Examples 1-1 to 1-53 is lighter and the 600cls capacity retention rate is higher, indicating that the electrolyte has a better wetting effect on the negative electrode sheet, and the lithium-ion battery has better lithium plating performance and cycling performance.

[0115] W×C Si The value of ×d / D usually affects the lithium plating performance and cycling performance of the lithium-ion battery. It can be seen from Examples 1-1 to 1-10 that when the value of W×C Si ×d / D is within the scope of the present application, the degree of lithium plating of the lithium-ion battery is lighter, and the 600cls capacity retention rate is higher, indicating that the electrolyte in the examples of the present application has a good wetting effect on the negative electrode sheet, and the lithium plating performance and cycling performance of the lithium-ion battery are good.

[0116] The thickness D of the second negative electrode material layer usually affects the lithium plating performance and cycling performance of the lithium-ion battery. It can be seen from Examples 1-1, 1-11 to 1-20 that when the thickness D of the second negative electrode material layer is within the scope of the present application, the degree of lithium plating of the lithium-ion battery is lighter, and the 600cls capacity retention rate is higher, indicating that the electrolyte in the examples of the present application has a good wetting effect on the negative electrode sheet, and the lithium plating performance and cycling performance of the lithium-ion battery are good.

[0117] The mass percentage content W of Si element in the second negative electrode material layer in the second negative electrode material layer usually affects the lithium plating performance and cycling performance of the lithium-ion battery. It can be seen from Examples 1-14, Examples 1-21 to Examples 1-28 that when the mass percentage content W of Si element in the second negative electrode material layer in the second negative electrode material layer is within the scope of this application, the degree of lithium plating of the lithium-ion battery is relatively light, and the capacity retention rate at 600 cls is relatively high, indicating that the electrolyte in the examples of this application has a good wetting effect on the negative electrode sheet, and the lithium plating performance and cycling performance of the lithium-ion battery are good.

[0118] The specific capacity C of the silicon-based material Si usually affects the lithium plating performance and cycling performance of the lithium-ion battery. It can be seen from Examples 1-14, Examples 1-29 to Examples 1-36 that when the specific capacity C of the silicon-based material Si is within the scope of this application, the degree of lithium plating of the lithium-ion battery is relatively light, and the capacity retention rate at 600 cls is relatively high, indicating that the electrolyte in the examples of this application has a good wetting effect on the negative electrode sheet, and the lithium plating performance and cycling performance of the lithium-ion battery are good.

[0119] The thickness ratio T of the second negative electrode material layer usually affects the lithium plating performance and cycling performance of the lithium-ion battery. It can be seen from Examples 1-1, Examples 1-37 to Examples 1-44 that when the thickness ratio T of the second negative electrode material layer is within the scope of this application, the degree of lithium plating of the lithium-ion battery is relatively light, and the capacity retention rate at 600 cls is relatively high, indicating that the electrolyte in the examples of this application has a good wetting effect on the negative electrode sheet, and the lithium plating performance and cycling performance of the lithium-ion battery are good.

[0120] The mass percentage content X of Si element in the second negative electrode material layer in the Si element of the negative electrode material layer usually affects the lithium plating performance and cycling performance of the lithium-ion battery. It can be seen from Examples 1-45 to Examples 1-53 that when the mass percentage content X of Si element in the second negative electrode material layer in the Si element of the negative electrode material layer is within the scope of this application, the degree of lithium plating of the lithium-ion battery is relatively light, and the capacity retention rate at 600 cls is relatively high, indicating that the electrolyte in the examples of this application has a good wetting effect on the negative electrode sheet, and the lithium plating performance and cycling performance of the lithium-ion battery are good.

[0121] The depth d of a single stripe usually affects the lithium plating performance and cycling performance of the lithium-ion battery. It can be seen from Examples 1-1 to Examples 1-53 that when the depth d of a single stripe is within the scope of this application, the degree of lithium plating of the lithium-ion battery is relatively light, and the capacity retention rate at 600 cls is relatively high, indicating that the electrolyte in the examples of this application has a good wetting effect on the negative electrode sheet, and the lithium plating performance and cycling performance of the lithium-ion battery are good.

[0122] Table 2

[0123]

[0124]

[0125] The width n of a single stripe generally affects the lithium plating performance and cycling performance of a lithium-ion battery. It can be seen from Example 1-1, Example 2-1 to Example 2-4 that when the width n of a single stripe is within the scope of this application, the degree of lithium plating of the lithium-ion battery is relatively light, and the capacity retention rate of 600 cls is relatively high, indicating that the electrolyte in the embodiments of this application has a good wetting effect on the negative electrode sheet, and the lithium plating performance and cycling performance of the lithium-ion battery are good.

[0126] The number of stripes, namely the values of a1, a2, and a3, on the second negative electrode material layer per 2 cm in each segment generally affects the lithium plating performance and cycling performance of a lithium-ion battery. It can be seen from Example 1-1, Example 2-5 to Example 2-6 that when the number of stripes, namely the values of a1, a2, and a3, on the second negative electrode material layer per 2 cm in each segment is within the scope of this application, the degree of lithium plating of the lithium-ion battery is relatively light, and the capacity retention rate of 600 cls is relatively high, indicating that the electrolyte in the embodiments of this application has a good wetting effect on the negative electrode sheet, and the lithium plating performance and cycling performance of the lithium-ion battery are good.

[0127] The length ratios of the first segment, the second segment, and the third segment generally affect the lithium plating performance and cycling performance of a lithium-ion battery. It can be seen from Example 1-1, Example 2-7 to Example 2-8 that when the length ratios of the first segment, the second segment, and the third segment are within the scope of this application, the degree of lithium plating of the lithium-ion battery is relatively light, and the capacity retention rate of 600 cls is relatively high, indicating that the electrolyte in the embodiments of this application has a good wetting effect on the negative electrode sheet, and the lithium plating performance and cycling performance of the lithium-ion battery are good.

[0128] It should be noted that in this article, relational terms such as first and second are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship or order between these entities or operations. Moreover, the term "comprising", "including" or any other variation thereof is intended to cover non-exclusive inclusion, so that a process, method or article including a series of elements not only includes those elements, but also includes other elements not expressly listed, or also includes elements inherent to such process, method or article.

[0129] Each embodiment in this specification is described in a related manner. For the same or similar parts among the embodiments, reference can be made to each other. The key point of each embodiment is to illustrate the differences from other embodiments.

[0130] The above are only the preferred embodiments of the present application and are not intended to limit the present application. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present application shall be included within the scope of protection of the present application.

Claims

1. A cylindrical secondary battery, comprising a negative electrode tab, the negative electrode tab including a negative electrode current collector and a negative electrode material layer located on at least one surface of the negative electrode current collector, the negative electrode material layer including a first negative electrode material layer and a second negative electrode material layer; The first negative electrode material layer is located between the negative electrode current collector and the second negative electrode material layer, and both the first negative electrode material layer and the second negative electrode material layer include a silicon-based material. Based on the mass of the negative electrode material layer, the mass percentage of Si element in the first negative electrode material layer is greater than that in the second negative electrode material layer; The second negative electrode material layer is provided with a plurality of stripes, the plurality of stripes extending along the width direction after the negative electrode tab is unfolded, and the plurality of stripes being spaced along the length direction after the negative electrode tab is unfolded.

2. The cylindrical secondary battery according to claim 1, wherein, In the thickness direction of the negative electrode tab, the thickness of the second negative electrode material layer is D μm, and the depth of a single stripe is d μm; Based on the mass of the second negative electrode material layer, the mass percentage content of Si element in the second negative electrode material layer is W, and the specific capacity of the silicon-based material is C Si mAh / g, 1.01 ≤ W × C Si × d / D ≤ 15.87, 10 ≤ D ≤ 55, 0.6% ≤ W ≤ 5%, 1300 ≤ C Si ≤ 1800.

3. The cylindrical secondary battery according to claim 2, wherein, 3.20 ≤ W × C Si × d / D ≤ 4.76。 4. The cylindrical secondary battery according to any one of claims 1 to 3, wherein, In the length direction after the negative electrode tab is unfolded, the second negative electrode material layer includes a first section, a second section, and a third section connected in sequence; Based on the length of the second negative electrode material layer, the length ratio of the first section is 10% to 30%, the length ratio of the second section is 40% to 80%, and the length ratio of the third section is 10% to 30%; The stripes on the first section have a first density, the stripes on the second section have a second density, and the stripes on the third section have a third density. The second density is greater than the first density, and the third density is less than or equal to the second density.

5. The cylindrical secondary battery according to claim 4, wherein, The number of stripes on the second negative electrode material layer per 2 cm in the first section is 1 to 3, the number of stripes on the second negative electrode material layer per 2 cm in the second section is 4 to 6, and the number of stripes on the second negative electrode material layer per 2 cm in the third section is 2 to 4.

6. The cylindrical secondary battery according to any one of claims 1 to 5, wherein, In the length direction after the negative electrode tab is unfolded, the width of a single stripe is n μm, 45 ≤ n ≤ 85.

7. The cylindrical secondary battery according to any one of claims 1 to 6, wherein, In the thickness direction of the negative electrode tab, the depth of a single stripe is d μm, 1 ≤ d ≤ 30.

8. The cylindrical secondary battery according to any one of claims 1 to 7, wherein, In the thickness direction of the negative electrode tab, the thickness of the second negative electrode material layer is D μm, 12 ≤ D ≤ 45.

9. The cylindrical secondary battery according to any one of claims 1 to 8, wherein, Based on the mass of the second negative electrode material layer, the mass percentage of Si element in the second negative electrode material layer is W, 1% ≤ W ≤ 2%.

10. The cylindrical secondary battery according to any one of claims 1 to 9, wherein, The specific capacity of the silicon-based material is C Si mAh / g, 1400 ≤ C Si ≤ 1600.

11. The cylindrical secondary battery according to any one of claims 1 to 10, wherein, Based on the thickness of the negative electrode material layer, the thickness ratio of the second negative electrode material layer is T, 40% ≤ T ≤ 80%.

12. The cylindrical secondary battery according to claim 11, wherein, 50%≤T≤75%。 13. The cylindrical secondary battery according to any one of claims 1 to 12, wherein, Based on the mass of Si element in the negative electrode material layer, the mass percentage of Si element in the second negative electrode material layer is X, 5% ≤ X ≤ 20%.

14. The cylindrical secondary battery according to claim 13, wherein, 8%≤X≤15%。 15. An electronic device, comprising the cylindrical secondary battery according to any one of claims 1 to 14.